2022
DOI: 10.3390/healthcare11010044
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Empowerment and Functioning and Disability in Older Japanese Patients: A Covariance Structure Analysis

Abstract: In the present study, 151 Japanese older adults aged over 65 years and admitted to recovery-phase rehabilitation facilities were enrolled to investigate the relationship between empowerment and contextual factors, functioning and disability, with structural equation modeling (SEM). The analysis included 151 patients aged 81.75 ± 7.15 years, including 54 males (35.76%) and 97 females (64.24%). The results of the SEM analysis showed that role presence (β = 0.45, p < 0.01) and family structure (β = 0.18, p = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…25 In the study by Tsubouchi et al, it was concluded that the role of the elderly person in society and the family, and the structure of family has important effects on empowerment. 26 It can be thought that this result found in the study is related to the fact that the majority of the elderly participating in the study had social security, about half of them had someone supporting their care, and a few of them lived alone.…”
Section: Discussionmentioning
confidence: 79%
“…25 In the study by Tsubouchi et al, it was concluded that the role of the elderly person in society and the family, and the structure of family has important effects on empowerment. 26 It can be thought that this result found in the study is related to the fact that the majority of the elderly participating in the study had social security, about half of them had someone supporting their care, and a few of them lived alone.…”
Section: Discussionmentioning
confidence: 79%